State-of-the-Art DC-DC Converters for Satellite Applications: A Comprehensive Review - Reshma Ravindran; Ahmed M. Massoud (Aerospace)
Future manned and deep space missions require an Electrical Power System (EPS) that can deliver high power while overcoming challenges like weight and volume constraints and the harsh space environment. A variety of DC-DC converters are employed to supply, store, and transmit power to various satellite subsystems. This paper identifies the design specifications of DC-DC converters for a range of satellite applications and offers a state-of-the-art review of non-isolated, isolated, and integrated topologies. Foreseeing the future of electric propulsion, various sources for electric propulsion are compared, and converters for electric propulsion are studied. The topologies are compared regarding practical parameters like reliability, modularity, redundancy, efficiency, and power density. Furthermore, an application-wise comparison of the topologies and the type of satellite they are suitable for is provided. Finally, the research gaps pertaining to various space applications, such as the design of DC-DC converters, electric propulsion, deep space exploration, electronic component selection, and space-based power satellites, are presented.